INTERNALISASI NILAI-NILAI BUDAYA JAWA DALAM PELAKSANAAN KONSELING INDIVIDU OLEH GURU BIMBINGAN DAN KONSELING - Mukaromah, Siti Tri; Wibowo, Agus; Pranoto, Hadi (Counseling Milenial (CM), 2023)
The aims of this study are to determine the value of mutual assistance which is internalized in the implementation of individual counseling for students at SMA Negeri 4 Metro. To find out the value of the community that is internalized in the implementation of individual counseling for students at SMA Negeri 4 Metro. To find out the value of the pillars that are internalized in the implementation of individual counseling for students at SMA Negeri 4 Metro. To find out the value of character (Tepa Selira) which is internalized in the implementation of individual counseling for students at SMA Negeri 4 Metro. To find out the value of courtesy (upload ungguh) which is internalized in the implementation of individual counseling for students at SMA Negeri 4 Metro. This research method uses qualitative research with descriptive research typeThe instrument in this study used interview sheets, observations, and documentation. Data analysis used inductive descriptive data analysis. The results of this study indicate that the form of mutual cooperation values ​​instilled in students includes group work. The form of community values ​​that are instilled in students are in the form of togetherness and brotherhood among school components. The form of the value of internalized harmony is in the form of mutual care and respect, avoiding misunderstandings that cause conflict. The form of tepa selira values ​​that are instilled in students include the teacher having to understand the situation and condition of the students. The forms of uploading values ​​that are instilled in students include attitudes, character, morals, and respect for others.